Scientometric Insights into Social Media Analytics: Trends and Impact in Communication Studies - Chaman, Sab M; Mueen, Ahmed KK (Information Research Communications, 2024)
This study provides an in-depth bibliometric view of social media analytics studies trends in communication science from 2011 to 2024 using data from the Web of Science citation index. Using bibliophily and VOSviewer as a visualization tool of our dataset, we examined the evolution trajectories of publication volume, citation performance and research networking. Out of 285 documents analyzed, it was found that the growth rate was at an average of 33.06% with a noticeable upward skew of the volume of publications after 2017. Findings indicate that the buoyant nature of research in this area can be attributed to cross-border collaboration of scholars, 38.6% of the papers were international co-authored and the average number of co-authors per document was 4.11. The field is considered to be well developed and intellectually safe with the average number of citations to papers amounting to 34.68 and the number of references used in the work being 17474. The study also looks into the research in this discipline represented through 1,093 author keywords underscoring the changing trends of research areas within social media analytics. These results contribute to ongoing communication studies, regarding the use of digital social media, by indicating the vast and increasing need for social media analytics.
Keywords: Social media Analytics; Communication Studies; Scientometric; Web of Science; VOSViewer